1992
DOI: 10.1177/002221949202500910
|View full text |Cite
|
Sign up to set email alerts
|

Specific Reading Impairments—Are They to Be Associated with Emotional Difficulties?

Abstract: The assumption that specific learning disabilities are not causally related to emotional disturbances is crucial for the cognitive research approaches that endeavor to isolate specific malfunctioning cognitive-computational processes. Because there are conflicting data regarding the emotional status of subjects with learning difficulties, the purpose of this study was the evaluation of the emotional status of subjects with specific learning difficulties in comparison with that of subjects from several relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…A growing number of studies have confirmed the role of DD as a risk factor for high levels of internalizing symptomatology in children and adolescents (Biederman et al, 1991;Cantwell and Baker, 1991;Faraone et al, 1993;Beitchman and Young, 1997;Bäcker and Neuhäuser, 2002; see Mugnaini et al, 2009 for a review). However, some studies reported no significant differences in emotional symptomatology between DD and controls (Jorm et al, 1986;Lamm and Epstein, 1992;Newcomer et al, 1995;Miller et al, 2005;Maag and Reid, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies have confirmed the role of DD as a risk factor for high levels of internalizing symptomatology in children and adolescents (Biederman et al, 1991;Cantwell and Baker, 1991;Faraone et al, 1993;Beitchman and Young, 1997;Bäcker and Neuhäuser, 2002; see Mugnaini et al, 2009 for a review). However, some studies reported no significant differences in emotional symptomatology between DD and controls (Jorm et al, 1986;Lamm and Epstein, 1992;Newcomer et al, 1995;Miller et al, 2005;Maag and Reid, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have failed to find differences in the emotional profile of subjects with and without SLD (Lamm & Epstein, 1992;Jorm, Share, Matthews, & McLean, 1986;Miller, Hynd, & Miller, 2005). Others have found only marginal differences in female participants but not in males (Heath & Ross, 2000).…”
mentioning
confidence: 99%
“…This may be due to less demand on reading skills after education is nished but may also be due to compensation for reading problems with age. Sex differences in the association between behaviour problems and dyslexia have been found in some (15) but not all studies (12,16).…”
mentioning
confidence: 99%